Intracellular iron accumulation throughout the progression of sepsis influences the phenotype and function of activated macrophages in renal tissue damage - Hanna, Mira; Akabawy, Ahmed M. A.; Khalifa, Mohamed Mansour; Elbaset, Marawan Abd; Imam, Reda Abdelnasser; Seddiek, Hanan (Frontiers in Physiology, 2025)
Sepsis, the most common cause of acute kidney injury, remains a major socioeconomic burden. A dysregulated immune response leads to progressive organ dysfunction. Although numerous inflammatory pathways were described, most are still vague and need to be studied in terms of the mechanisms to improve the therapeutic intervention. We tackled the relationship between intracellular iron overload and macrophage polarization within 6, 24, and 72 h of sepsis induction. In our study, sepsis-induced kidney injury was caused by using the cecal ligation and puncture (CLP) model. Our results indicated severe renal tissue damage with a progressive increase in serum BUN and creatinine with architectural tissue damage and positive PAS staining. There was increased expression of CD8+ CD68+ M1 macrophage markers with upregulation of iNOS and co-expression of CD163+. Alternatively, Arg1+ Fizz1+ M2 macrophage markers were downregulated with increased iNOS/Arg1 ratio. TFR1, cubilin, and DMT1, as iron transport systems, were increased compared to sham but were significant after 72 h, while ZIP8 showed no significant change. There was a correlation between iron overload and M1 macrophage polarization with CD163+ phenotype, together with fibrotic changes. The intracellular iron overload with downregulation of ferritin was strongly related to macrophage polarization that was exaggerated at 72 h. Finally, early introduced therapy to target free iron during sepsis is a proposed novel solution for protecting the renal tissue from acute injury due to macrophage activation that may end up with chronic kidney injury, if not mortality.